Narrative Text Translation by the Students of English Education Study Program - Muhammad Zein Hardiansyah; Anjar Kusuma Dewi; Sriati Usman (Institut Agama Islam Negeri Palopo, 2022)
This research aims to find out the translation methods that are mostly used by students of the English Education Study Program. Kind of this research is qualitative research. The subjects in this research were 10 students of Tadulako University specifically in English Education Study Program who had enrolled in the Translation and Interpretation course and selected using the snowball technique. The instrument in this research is the translation test. In analyzing the data, the researcher used the Newmark translation method theory. The results of this research indicate that there are only five translation methods applied by students in translating a text. The translation method that is mostly used by students is free translation method. The second is communicative translation method. The third is idiomatic translation method. Then, the fourth is literal translation method.The last position is faithful translation method. Meanwhile, it was also identified methods that were not applied by students, including word-for-word translation method, semantic translation method, and adaptation translation method. So it can be concluded the free translation method is a translation method that is mostly applied by English education students at Tadulako University. The results of this research also indicate that the students applied more than one method in translating a text dan they tend to apply translation methods that emphasize the target language